Set and Setting in the Santo Daime - Hartogsohn, Ido (Frontiers in Pharmacology, 2021)
Set and setting is a fundamental concept in the field of psychedelic drug research, which points to the profound dependence of psychedelic effects on psychological, social, and cultural factors. Santo Daime is a Brazilian rainforest religion, which makes elaborate use of ordering principles, techniques, and symbology to shape and direct the effects of the hallucinogenic brew ayahuasca. This paper systematically explores the tapestry of (inter alia) symbolic, social, cultural, psychological, aesthetic and musical elements which participate in the shaping of the psychedelic experience in the context of the Santo Daime ayahuasca religion.